Higher dietary inflammatory index is associated with increased all-cause mortality in adults with chronic kidney disease - Yan, Li-Jun; Zhang, Fei-Ran; Ma, Chan-Shan; Zheng, Yang (Frontiers in Nutrition, 2022)
Background. Diet property grounded on inflammatory potential, evaluated by the dietary inflammatory index(DII), has been proven connecting with mortality, while studies from adults with chronic kidney disease(CKD)are scarce. Objective. The purpose of this research was to evaluate the interrelationships between DII and all-cause mortality among adults with CKD. Methods. In the National Health and Nutrition Examination Survey(NHANES) 2001-2006, we identified and evaluated data of 4554 adults with CKD. DII scores were calculated from 24 hours dietary consumption at baseline. Vital status was followed through December 31,2015.The association of all-cause mortality with DII was assessed using the Kaplan-Meier curve and Cox regression analysis. Results. After an average follow-up of 132.103 months, a total of 1246(27.36%) deaths were recorded.The death rate in the DII tertile categories were 24.04%, 26.81% and 31.23%, respectively. Kaplan-Meire curve showed elevated death risks for the high DII tertile as compared to the low DII tertile. After we adjusted for a broad range of possible confounders, the estimation between extreme tertiles of DII scores presented a positive and significant association with all-cause mortality(HR:1.21, 95%CI:1.05-1.39). Conclusions. Our results confirm the hypothesis that proinflammatory diets contribute to increase all-cause mortality in adults with CKD.